Penerapan Metode Case Base Reasoning Dalam Diagnosa Penyakit dan Hama pada Tanaman Hortikultura - Dasril Aldo; Yohani Setiya Rafika Nur; Andre Citro Febriliyan Lanyak; Filfimo Yulfiz Ahsanul Hulqi; Rania Nur Hikmah (Forum Kerjasama Pendidikan Tinggi, 2022)
Horticultural products are products from the agricultural sub-sector with potential and prospects for development. Horticultural products consist of medicinal products, fruit, vegetables, and ornamental plants. However, some farmers are still not optimal in getting results from their cultivation because they do not understand how to control pests and diseases of horticultural crops. This causes the plant to be susceptible to various diseases. Identification of diseases in these plants is often done manually so it takes a long time. The development of computer technology can be utilized in various branches of science, one of which is the field of artificial intelligence. Expert systems are included in one of the scientific branches of the current artificial intelligence program. Expert systems have the ability to solve a particular problem, usually requiring an expert from an expert. The method that will be used is the case-based reasoning (CBR) approach. This study aims to help farmers diagnose diseases and pests, so that they are more optimal and on target in controlling. In the implementation of the expert system with the CBR method, a diagnosis will be obtained, and it will be recommended for plant control. Case Based Reasoning method is used to process 10 data. This method will process data in the form of symptoms seen in horticultural plants. The test results obtained a percentage value of 80%. Therefore, the application of the Case Based Reasoning method is very relevant in the Diagnosis of Diseases and Pests in Horticultural Crops.